2021
DOI: 10.1108/arj-06-2020-0140
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bank stability in a small island economy: a study of Fiji

Abstract: Purpose This study aims to examine the determinants of bank stability based on three measures of bank stability while accounting for key bank-specific, macro-finance and structural variables. The aim is to underscore key indicators of stability that can be tracked by analysts, bank managers and regulators, especially in small economies such as Fiji. Design/methodology/approach The sample comprises a balanced panel of seven banking and financial institutions over the period 2000-2018. For consistency of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Besides, Ibrahim and Rizvi (2017) stated that the positive association between bank size and the financial stability of the banking sector due to the large banks have greater potential to achieve economies of scale because they have the resources to capably carry out intermediation, monitoring, pricing and diversification strategies. In addition, Chand et al (2021) figure that bank size is a positive significance on the bank performance which implies that the larger operations bank of Fiji countries will be more stable and able to survive longer than the small operations bank.…”
Section: Problem Statementmentioning
confidence: 98%
“…Besides, Ibrahim and Rizvi (2017) stated that the positive association between bank size and the financial stability of the banking sector due to the large banks have greater potential to achieve economies of scale because they have the resources to capably carry out intermediation, monitoring, pricing and diversification strategies. In addition, Chand et al (2021) figure that bank size is a positive significance on the bank performance which implies that the larger operations bank of Fiji countries will be more stable and able to survive longer than the small operations bank.…”
Section: Problem Statementmentioning
confidence: 98%
“…Individuals receiving remittances often deposit these funds into their local bank accounts, expanding the bank's pool of funds and enabling the bank to extend loans and engage in investment activities. In one study on banks in Fiji, Chand et al (2021) found a positive correlation between remittances and bank stability, and in another (Chand et al 2023), they observed a negative association between remittances and non-performing loans, indicating that remittances support banking operations. Similarly, Ayhan and Toufaili (2021) examined the relationship between remittances and bank profitability for banks in Lebanon, and they found a positive relationship.…”
Section: Remittances (Rems)mentioning
confidence: 99%
“…Following a few recent studies (Theiri and Hadoussa 2023;Chand et al 2021Chand et al , 2023, we specify the profitability model as follows:…”
Section: Model Specificationsmentioning
confidence: 99%
“…Joaqui- Barandica et al (2021) examined the relationship between commonality, macroeconomic factors and bank profitability, while the study by Chand et al (2021) analysed the determinant of bank stability in a small Island economy, providing evidence from Fiji.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%